Differential Analysis of Gut Microbiota Correlated With Oxidative Stress in Sows With High or Low Litter Performance During Lactation - Wang, Hao; Ji, Yongcheng; Yin, Cong; Deng, Ming; Tang, Tianyue; Deng, Baichuan; Ren, Wenkai; Deng, Jinping; Yin, Yulong; Tan, Chengquan (Frontiers in Microbiology, 2018)
Gut microbiota has been suggested to play a critical role in maternal metabolic, oxidative stress responses and offspring growth. However, whether the gut microbiota and oxidative stress status of the sows affect the litter performance during lactation is unclear. A total of 66 Yorkshire sows were identified as high (H) or low (L) litter performance sows based on litter weight at day 21 of lactation. 10 sows per group with similar parity, backfat thickness, and litter weight after cross-foster from the H or L group were collected randomly to analyze the oxidative stress and gut microbiota during lactation. Result showed that the serum concentration of total antioxidant capacity was higher in the H group, while 8-hydroxy-deoxyguanosine and thiobarbituric acid reactive substances were lower in the H group at farrowing. Four distinct clusters of bacteria were related to litter performance and reproductive periods of sows. There were 12 differentially abundant taxa during gestation and 13 taxa during lactation were identified as potential biomarkers between the H group and L group. Moreover, litter performance and antioxidant capacity of sows were positively correlated with Bacteroides_f__Bacteroidaceae, but negatively with Phascolarctobacterium and Streptococcus. In conclusion, this study found that gut microbiota and oxidative stress were significantly correlated with the litter performance of sows during lactation.